Konsep Silaturahim Dalam Alquran Dan Implikasinya Terhadap Pendidikan Agama Islam Di Sekolah - Dewi, Utami; Asyafah, Abas; Anwar, Saepul (Civilization Research: Journal of Islamic Studies, 2022)
Education has to result in qualified generation and strong personality of human being. This study is underpined by a moral of students these days. This research is purposed to investigate a concept of ṣilaturaḥim in Alquran relating to the implication for Islāmic education at school. This research uses qualitative approach and using mauḍu’ī to identify and analyze all term of Ṣilaturaḥim in Alquran. The data of this research is chosen tafsīr Alquran relating to the topic by mufasirin. This research is based on the meaning of ṣilaturaḥim in Alquran will obtain 1) as a guide for ‘aqῑdaħ, 2) generating devotion to Allāh, 3) deciding heirs, 4) trusteeship, 5) creating essential relationships among society, 6) `akhlāqul karimaħ. The standpoint of Ṣilaturaḥim in Alquran can lead to acquire raḥmaħ, kept away from adzab, help each other, gain livelihood, and have a long life. Based on this research, the concept of ṣilaturaḥim in Alquran has implications for educators, those are educators, students, curriculum, function, principles, and teaching method orientation.